Different associated factors of subjective cognitive complaints in patients with early and advanced Parkinson's disease - Huang, Juan; Chen, Lin; Hu, Binbin; Wang, Hui; Zhang, Xinyue; Tian, Xingfu; Wang, Shu; Huang, Wei (Frontiers in Aging Neuroscience, 2023)
Subjective cognitive complaints (SCCs), defined as cognitive decline reported by subjects or their informants, are common in the early stage of Parkinson's disease (PD). Previous studies have shown a significant association between SCCs and non-motor features as well as objective cognitive decline in PD patients. However, the discrepancy in SCC prevalence and SCC-related factors between patients with early PD and those with advanced PD remains poorly understood. We recruited a total of 114 and 69 early PD patients and advanced PD patients, respectively. Univariate and multivariate logistic regression analyses were performed for early PD and advanced PD patients. The prevalence of SCCs in the early PD and advanced PD groups was 60.5 and 68.1%, respectively. In the early PD group, the presence of SCCs in early PD participants was significantly associated with a higher nonmotor symptoms questionnaire (NMSQ) score (OR = 1.05, 95% CI = 1.00–1.10, p = 0.040). SCCs in the advanced PD group were related to lower attention scores (OR = 0.24, 95% CI = 0.05–0.90, p = 0.043) and lower visuospatial/executive abilities scores (OR = 0.18, 95% CI = 0.04–0.86, p = 0.032). The prevalence and SCC-related factors are distinct in early PD and advanced PD. These findings suggest that SCCs in PD patients with different disease statuses appear to have different related factors that may depend on different disease severities.